Language diversity, language disorder, and fetal alcohol spectrum disorder among youth sentenced to detention in Western Australia - Kippin, N.; Leitao, Suze; Watkins, R.; Finlay-Jones, A.; Condon, C.; Marriott, R.; Mutch, R.; Bower, C. (Pergamon, 2018)
Copyright © 2018 The Authors. Published by Elsevier Ltd.. All rights reserved. BACKGROUND: While studies confirm high prevalence of language disorder among justice-involved young people, little is known about the impact of Fetal Alcohol Spectrum Disorder (FASD) on language among this population. It is also not clear how language skills vary according to language diversity in Australian youth justice settings, where a disproportionate number of justice-involved youth are Aboriginal and may not speak Standard Australian English (SAE) as their first language. Language skills are important to understand, as language disorder and language difference can lead to a mismatch between the communication skills of a young person and the communication skills of the justice workforce with whom they are communicating. In the highly verbal environments that are common to justice systems, language disorder and language difference may result in a young person misunderstanding legal information and expectations placed on them and not being adequately understood by the justice workforce. METHODS: This study examined the language skills of 98 young people sentenced to detention in Western Australia (WA), who participated in a cross-sectional study examining the prevalence of FASD. Language skills assessed using standardised and non-standardised tasks were analysed by the three major language groups identified: speakers of SAE, Aboriginal English and English as an additional language. RESULTS: We identified rich diversity of languages, and multilingualism was common. Most young people for whom English was not their first language demonstrated difficulties in SAE competence. Further, nearly one in two young people were identified with language disorder - over half of whom had language disorder associated with FASD. CONCLUSIONS: This study has documented language diversity and the prevalence of language disorder associated with FASD among a representative sample of youth sentenced to detention in WA. Results underscore the need for the justice workforce to consider language difference when working with justice-involved youth, as well as language disorder and FASD. The findings also demonstrate the need for speech pathology to be embedded as core service in youth justice systems, working in collaboration with local cultural and language advisors and accredited interpreters. This can better enable appropriate identification of and response to communication and associated rehabilitation needs of young people navigating youth justice systems.